Experimental study on the shrinkage behaviour of steel concrete composite slab. Issue 2 (1st September 2021) - Yamamoto, Masashi; Imagawa, Yusuke; Ohyama, Osamu
Abstract: Steel concrete composite slabs are widely adopted in civil engineering and their numbers are rapidly increasing in Japan. A steel concrete composite slab is connected between concrete and a bottom steel plate by a shear connector. FaB‐Tec Japan Corporation developed a rigid type of shear connecter with a pipe that passes through the long hole on the steel rib. The load‐carrying capacity and durability of this design have been confirmed to be equal to or more than those of the headed stud and perfobond‐rib because the long hole of the steel pipe is filled with concrete. However, the time‐dependent behaviour, especially drying shrinkage, of this type of slab remains unclear. A steel concrete composite slab contains more steel than reinforced and prestressed concrete slabs; the effect of drying shrinkage is therefore expected to be greater owing to the steel restraint. To address this question, drying shrinkage tests were performed on steel concrete composite slabs and reinforced slabs. The change of stress resultants induced on the concrete, reinforcing bar and bottom steel plate was obtained by solving the simultaneous equation derived from the equilibrium conditions for stress resultants and the compatibility condition of strain and curvature.